Rain Attenuation Analysis using Synthetic Storm Technique in Malaysia - Lwas, A.K.; Islam, Md. Rafiqul; Chebil, Jalel; Habaebi, Mohamed Hadi; Ismail, Ahmad (2013)
Generated rain attenuation time series is required for investigating the rain fade characteristics in the lack of real fade measurements. A suitable conversion technique can be applied to rain rate time series to produce rain attenuation data and be utilized to understand the rain fade characteristics the problem. This paper focused on applicability of synthetic storm technique (SST) to convert available data to rain attenuation time series. Its performance is assessed for time series generation over Kuala Lumpur, a tropical location in Malaysia. From the analysis, it is found that SST gives satisfactory results to estimate the rain attenuation time series from the rain rate measurements over this region.